Development and characterisation of cysteine-based gold electrodes for the electrochemical biosensing of the SARS-CoV-2 spike antigen - Olgac, Nursel; Sahin, Yucel; Liv, Lokman (ROYAL SOC CHEMISTRY, 2022)
This article describes three novel electrochemical biosensing platforms developed to determine the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) spike antigen protein: glutaraldehyde, SARS-CoV-2 spike antibody and bovine serum albumin; N,N-dicyclohexyl carbodiimide/4-(dimethylamino)pyridine functionalised SARS-CoV-2 spike antibody and bovine serum albumin; and 1-ethyl-3-[3-dimethylaminopropyl]-carbodiimide hydrochloride/N-hydroxysuccinimide functionalised SARS-CoV-2 spike antibody and bovine serum albumin modified cysteine-based gold-flower modified glassy carbon electrodes. Two of the produced biosensors having better signals were used to determine the SARS-CoV-2 spike antigen in spiked-saliva and clinical samples containing gargle and mouthwash liquids and characterised using cyclic voltammetry, scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy. The study provides highly significant information in terms of how coupling reagents ought to be used with linkers consisting of both amine and carboxylic acid terminals (i.e. cysteine). The electrochemical cathodic signals based on antibody-antigen protein interactions at approximately -270 mV were evaluated as a response using square wave voltammetry, and they increased in proportion to the SARS-CoV-2 spike antigen. The limit of detection values were 0.93 and 46.3 ag mL(-1) in a linear range from 1 ag mL(-1) to 100 pg mL(-1) and from 100 ag mL(-1) to 10 ng mL(-1) and the recovery and relative standard deviation values for spiked-saliva samples were 99.50% and 99.40%, and 3.87% and 0.13% for BSA/S-AB/GluAl/Cys/Au/GCE and BSA/S-AB/f-Cys/Au/GCE, respectively. The results showed that both biosensing platforms could be selectively and accurately used to diagnose COVID-19 in RT-PCR-approved clinical samples.
Keywords: LATERAL FLOW IMMUNOASSAY; RAPID DETECTION; GRAPHENE; Chemistry